ANALISIS PENDAPATAN RETRIBUSI DALAM MENUNJANG PENDAPATAN ASLI DAERAH (PAD) KOTA METRO - Diah Rosanti (Akuisisi: Jurnal Akuntansi, 2016)
In the framework of the implementation of regional autonomy in accordance with the Act-Act 32 of 2004 on local government. Local governments are required to be able to organize and manage his household broadly and comprehensively based on existing regulations and develop and increase local revenue. The purpose of this study was to determine how much contribution levy of public services, business services, licensing certain to support the Local Revenue Metro City. The method used in this research is descriptive quantitative method is to do research on the object of the research that produced the data - the data information that is associated with the research that will be studied.The contribution of each type of area to PAD revenues in the period 2010 to 2014 fiscal year very flukuatif. Contributions contained in a levy of General Services is the average-average contribution of five years by 27%, the levy Business Services 4%, Levy Licensing Certain 2%, while 67% is the result of PAD others sourced from the Hotel Tax, Amusement Tax, Advertisement Tax, Tax Street Lighting (PLN and ULC Siwo Mego), Income Tax Minerals Group C and Tax concession Swallow nests and Seriti.  Keywords: Revenue, Levy, PAD